Gender and Financial Performance in Smes in Emerging Economies - Espinosa-Mendez, C (Emerald Group Holdings Ltd., 2022)
Purpose: The purpose of this paper is to investigate how chief executive officer (CEO) gender relates to financial performance in small and medium enterprises (SMEs) in a Latin American emerging economy like Chile. Design/methodology/approach: The authors apply a questionnaire on a sample of 188 SMEs in Chile in 2017. The authors apply multiple ordinary least squares regression models to test the effects of CEO gender on SME performance using the industry location indicators to account for unobserved heterogeneity in the sample. As a robustness test the authors use hierarchical regression analysis. Findings: The authors find a positive relationship between the presence of female CEOs and firm performance. Then, when probing whether the sociodemographic characteristics of the CEO are related to firm performance or moderate the gender-performance relationship, the authors do not find statistically significant evidence that these types of characteristics affect the performance of SMEs. Originality/value: To the best of the authors’ knowledge, the present study is the first to investigate the relationship between CEO gender and financial performance of SMEs in an emerging Latin American economy. The study contributes to the general literature by reporting comparable evidence with studies in developed economies. © 2022, Emerald Publishing Limited.